قراءة فى علاقة المفتى بمراكز القرار فى الدولة العثمانية إبان القرن 16 م. : شيخ الاسلام ابو السعود أنموذجا - ابن موسى، فيصل (جامعة الجلفة, 2018)
تهدف هذه الدراسة إلى الكشف عن طبيعة العلاقة التي جمعت بين سلطة العلماء والمفتين والفقهاء الممثلين بشخصية شيخ الإسلام بمختلف مراكز القرار بالدولة العثمانية خاصة عندما بدأ يبرز منحى جديد لمسار وظيفة الإفتاء في الدولة العثمانية، وأصبح الفقيه يدقق بشكل أكبر في القرارات والقوانين التي يصدرها السلاطين، ويعد شيخ الإسلام أبو السعود أفندي واحدا من أهم الشخصيات الفاعلة التي لعبت دوراً فاعلاً في مسار وطبيعة هذه العلاقة من خلال الكم الهائل من الفتاوى الشرعية التي كان يقررها في مختلف المجالات السياسية والاجتماعية والاقتصادية والثقافية..
This study aims to reveal the nature of the relationship that collected between the authority of scholars and muftis and jurists representatives personality Shaykh al- Islam in various decision centers of the Ottoman Empire, especially when on a distinguished road a new turn to the path of the advisory function in the Ottoman Empire, and became a jurist more checks in the decisions and laws issued by the sultans, is Shaykh al-Islam Abu Saud Effendi, one of the most important actors figures who played an active role in the course and nature of this relationship through the vast amount of legitimate fatwas, which was decided in the various political, social, economic and cultural fields....
Keywords: الدولة العثمانية -- مفتى الدولى -- السلطة الحاكمة -- التاريخ الاسلامى -- أبو السعود، محمد، ت. 982 هـ